(untitled) (European Journal of Marketing and Economics, 2023)
Word of Mouth (WOM) become more significant nowadays with the raise of social media platforms, and internet. Therefore, we experience a shift of communication power from company towards masses. Customers share their own experiences on internet and that makes obvious the need to reconsider many practices. Information which exists and is uploaded on internet stands among the catalyzers of the power shifting that occurred. It is then obvious the shift of power from companies towards customers. Marketing experienced a major shift in its mindset. Brand choice, and value do not withstand apart, and critical elements such as relationships, and the cost of jumping in another relationship must be taken in consideration too. In this context, the need to consider brand management from a Service Dominant Perspective emerges. Not only brand value co-creation but also brand value co-evaluation has become concerning for firms in today`s dynamic context.